Low-energy high-current electron beam treatment of composite coatings based on diatomite and ZrO2 particles; Letters on Materials; Vol. 14, iss. 3 - Sedelnikova M. B. Maria Borisovna; Kashin A. D. Aleksandr Daniilovich; Uvarkin P. V. Pavel Viktorovich; Sharkeev Yu. P. Yury Petrovich; Luginin N. A. Nikita Andreevich; Khimich M. A. Margarita Andreevna; Ivanov K. V. Konstantin Veniaminovich (2024, 2024)
Title screen